The Basic Components Of The Sports Shows From The - Specialists’ Point Of View In Syria - عجيب شيريهان (Latakia University Journal -Medical Sciences Series, 2022)
This study aims to identify the basic components of the sports shows and to determine the most important component . The descriptive method is used with a questionnaire includes 13 of the sports show component . the questionnaire distributed on the sample of the study which includes 10 sports show’s specialists and it aimed to a simple random sample of 42 person . The study concludes that the important components are : music , costumes, performance , formations, time and the space of the show. And it shows that sport shows has a very important role of making individuals do more practice and it concludes that music is the most important component among all components.